Barbarian Digital Society: A Legal Philosophy Perspective on Efforts to Overcome the Moral Degradation of Indonesian Netizens - Ferry Irawan Febriansyah; Aldo Redho Syam; Vivi Ayudya Permatasari (NOVUM : JURNAL HUKUM, 2024)
The "Digital Barbarian Society" phenomenon occurs when Indonesian society suffers moral degradation in its activities on social media. Contradicts Indonesian society's culture, which highly values politeness and moderation. This normative legal research emphasizes philosophical, conceptual, and legislative approaches. The research findings confirm that the phenomenon of "Digital Barbarian Society" in Indonesia, particularly on social media, is triggered by a combination of factors such as the rapid development of digital technology without adequate digital literacy and ethics, the digital access gap, socio-psychological pressure, and the widespread dissemination of misinformation and hoaxes that lead to rudeness and chaos in cyberspace. From a legal philosophy perspective, the effort to regulate must go beyond mere punishment by emphasizing the formation of ethical awareness and the internalization of digital civility values rooted in society's legal culture. The ratification of the new Criminal Code and the revision of the ITE Law provide a more relevant and responsive legal basis for digital dynamics by balancing freedom of expression and the protection of public rights. Legal philosophy serves as the moral and social foundation that guides the application of digital law to achieve comprehensive digital justice and ethics